2016
DOI: 10.1111/avsc.12235
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐dependent effects of coppicing on the species pool of late successional beech forests in the central Apennines, Italy

Abstract: 43Question: We study the effect of traditional coppicing and its abandonment on community 44 structure and plant diversity at various scales. The aim is to compare active and abandoned beech 45 coppices in terms of: (i) structural features (ii) total, understory and overstory plant diversity across 46 a range of spatial scales (iii) species richness of beech forest specialist species. 47Location: Monti Sibillini, Central Apennines, Italy. 48Methods: We applied a multiscale approach working in parallel at fine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 45 publications
0
17
0
2
Order By: Relevance
“…The management plan is devoted to protecting the natural processes that have been underway since the 1960s, when traditional management began to be abandoned, leading to natural succession. Previously, the grasslands had been managed as sheep-pastures, and forests had been coppiced with a rotation cycle of about 25 years (Campetella et al 2016).…”
Section: Study Areamentioning
confidence: 99%
“…The management plan is devoted to protecting the natural processes that have been underway since the 1960s, when traditional management began to be abandoned, leading to natural succession. Previously, the grasslands had been managed as sheep-pastures, and forests had been coppiced with a rotation cycle of about 25 years (Campetella et al 2016).…”
Section: Study Areamentioning
confidence: 99%
“…Now, after ten years of ecological research in the same study area we investigated changes that have occurred in understory species composition, particularly of beech specialist species, because this specific pool of understory plants has proven to be a good indicator of the functional state of the forest (Bartha et al, 2008;Canullo et al, 2011;Campetella et al, , 2016Canullo et al, in press). …”
Section: Vegetation Surveysmentioning
confidence: 99%
“…The coppice rotation time is usually short (about 15-30 years), and yet this regime of relatively intense disturbance appears to help preserve the system's plant biodiversity , including rare ground flora species of considerable conservation interest (Ash and Barkham, 1976;Hölscher et al, 2001;Decocq et al, 2004Decocq et al, , 2005Bartha et al, 2008;Kopecky et al, 2013). In particular, Campetella et al (2016) demonstrated that the functional group of late successional beech forest species (beech specialist species) can largely persists in a coppiced landscape.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations